Protective efficacy of pirfenidone in rats with pulmonary fibrosis induced by bleomycin - Gul, Sule; Cörtük, Mustafa; Akanıl Fener, Neslihan; Yavuzsan, Eminegül; Eren, Ramazan; Baydili, Kursad Nuri; Çekmen, Mustafa Baki; Cetinkaya, Erdogan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background: Bleomycin causes increased production of reactive oxygen species, leads to pulmonary toxicity, fibroblast activation, and fibrosis.Objectives: This study aimed to evaluate the protective effect of pirfenidone on bleomycin-induced lung toxicity in rats.Methods: Twenty-eight adult rats were randomly divided into 3 groups; Bleomycin (B group, n=10), Bleomycin and Pirfenidone (B-PND group, n=13), and the control group (n=5). The bleomycin regimen was administered for 9 weeks. Pirfenidone was administered at 100 mg/kg daily. Total antioxidant level (TAS), total oxidant level (TOS), tumor necrosis factor (TNF-α), transforming growth factor (TGF-β1), matrix metalloproteinase-2 (MMP-2), plasminogen activator inhibitor (PAI) levels were studied. Histopathologically, sections were stained with Hematoxylin-eosin and Masson-trichrome for grading-scoring according to the Ashcroft score.Results: Stage 3 fibrosis was observed in 50% of the B group rats, stage 3 and higher fibrosis was never detected in the B-PND group and the difference was statistically significant (p=0.003). When evaluating tissue inflammation, the inflammation was higher in the B-PND group than in the other groups (p